STUDENTS AND COLLEGE PROFESSORS’ PERCEPTION ABOUT THE ACCOUNTANT PROFESSION: A STUDY BASED ON THE THEORY OF STEREOTYPES - Splitter, Karla (2014)
Studies indicate that the Accounting professionals have been the most concerned with the public image in recent years and that understanding the external images of accountants if important to judge their roles in a broader social context. This study aimed to identify and analyze the perceived image of the accountants’ professional activity among students and professors from five undergraduate courses. The opinions declared see it as an uninteresting activity, involving repetitive activities, which complies with standards and involves many calculations. In addition, the professionals have been considered introspective and hardly critical and communicative. The accountants are seen as professionals without a business view, hardly participatory or involved in management and not very up-to-date; greatly uses logic and forgets about people; simply complies with standards and solves operational issues. As regards the profession itself, it is perceived as involving calculations and mathematics and related to fiscal and tax aspects, mainly the Income Tax Declaration. Therefore, it cannot be denied that there is a stereotyped perception of this professional, as the accountants remain linked to the image of bookkeepers, merely related to fiscal requirements.